THE ROLE OF LITERATURE IN STRENGTHENING FRIENDSHIP BETWEEN NATIONS ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2025)
his article emphasizes how literature has functioned as long vital medium for strengthening connections between nations. Literary works help to break down assumptions and foster empathy across cultural barriers by providing insights into varied histories, cultures, and beliefs.